2010
DOI: 10.1007/s00262-010-0877-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of radiotherapy on NKT cells in patients with advanced head and neck cancer

Abstract: NKT cells are relatively resistant to radiation and might therefore be suitable for adjuvant immunotherapy to eradicate remnant cancer cells in patients who have undergone radiation therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…These results indicated that the administration of α-GalCer-pulsed APCs via the nasal submucosa was a better option for HNC patients. We also confirmed that the number and function of iNKT cells were not affected by radiation therapy, suggesting that iNKT cell based immunotherapy might be an adjuvant treatment of radiation therapy for advanced HNC patients ( 23 ).…”
Section: Introductionsupporting
confidence: 72%
“…These results indicated that the administration of α-GalCer-pulsed APCs via the nasal submucosa was a better option for HNC patients. We also confirmed that the number and function of iNKT cells were not affected by radiation therapy, suggesting that iNKT cell based immunotherapy might be an adjuvant treatment of radiation therapy for advanced HNC patients ( 23 ).…”
Section: Introductionsupporting
confidence: 72%
“…However, studies of firstdegree relatives of SLE patients suggest that iNKT cell dysfunction precedes autoimmunity, which is suggestive of a causative role in disease (14). Similarly, various solid-state and hematological cancer patients were shown to have reductions in iNKT cell numbers and function, which correlated inversely with prognosis (15)(16)(17)(18)(19)(20)(21). iNKT cells also were shown to play a regulatory role in other autoimmune disorders.…”
mentioning
confidence: 99%
“…As NKT cells are sharing some receptors and common features with T lymphocytes and NK cells they provide a functional link between the innate and adaptive antitumor immunity [35,36] and play crucial roles in immune regulation and surveillance against cancer [37]. Kobayashi et al described the ability of radiotherapy to improve proliferation and antitumor immunity of NKT cells [38]. In our SCCHN cohort, especially patients with locoregional recurrences, exhibited increased NKT cell levels at diagnosis which further increase throughout therapy as compared to controls.…”
Section: Discussionmentioning
confidence: 56%